THE INFLUENCE OF TGT COOPERATIVE LEARNING ASSISTED BY WORDWALL ON STUDENTS’ LEARNING OUTCOMES IMPROVEMENT - Anisah Safaatin; Surawan; Rita Yuliastuti (Universitas Muhammadiyah Metro, 2026)
This research is motivated by the low mathematics learning outcomes of students caused by the lack of variation in models and learning media used by teachers. The purpose of this study was to determine the influence, magnitude of influence, improvement and magnitude of improvement in student learning outcomes through the application of the TGT (Team Games Tournament) type cooperative learning model assisted by wordwall media. This study used a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design. The sample consisted of two classes, namely class VIII-C as the experimental class and class VIII-F as the control class and sampling using random sampling techniques. Data collection techniques used in the form of pretest and posttest essay tests. Data analysis using the t-test to determine the difference in learning outcomes between the experimental and control classes, the effect size test to determine the magnitude of the effect of the treatment, and the N-Gain test used to measure the magnitude of the increase in learning outcomes. The results of this study indicate a significant influence with an effect size value of 0,39% indicating a high influence and an N-Gain of 0.719246 shows that there is a significant increase for the experimental class. Thus, the cooperative learning model of the TGT (Team Games Tournament) type assisted by wordwall media has proven to be influential and effective in improving mathematics learning outcomes significantly. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar matematika siswa yang disebabkan oleh kurangnya variasi model dan media pembelajaran yang digunakan oleh guru. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh, besarnya pengaruh, peningkatan dan besarnya peningkatan hasil belajar siswa melalui penerapan model pembelajaran kooperatif tipe TGT (Team Games Tournament) berbantuan media wordwall. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kuasi eksperimen, khususnya pretest-posttest control group design. Sampel terdiri dari dua kelas, yaitu kelas VIII-C sebagai kelas eksperimen dan kelas VIII-F sebagai kelas kontrol dan pengambilan sampel menggunakan teknik random sampling. Teknik pengumpulan data yang digunakan berupa tes essay pretest dan posttest. Analisis data menggunakan uji-t untuk mengetahui perbedaan hasil belajar antara kelas eksperimen dan kelas kontrol, uji effect size untuk mengetahui besarnya pengaruh perlakuan, dan uji N-Gain yang digunakan untuk mengukur besarnya peningkatan hasil belajar. Hasil penelitian ini menunjukkan adanya pengaruh yang signifikan dengan nilai effect size sebesar 0,39% yang menunjukkan pengaruh yang tinggi dan N-Gain sebesar 0,719246 menunjukkan adanya peningkatan yang signifikan untuk kelas eksperimen. Dengan demikian, model pembelajaran kooperatif tipe TGT (Team Games Tournament) berbantuan media wordwall terbukti berpengaruh dan efektif dalam meningkatkan pembelajaran matematika.